2023
DOI: 10.1038/s41598-023-40381-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel disulfidptosis and glycolysis related risk score signature for prediction of prognosis and ICI therapeutic responsiveness in colorectal cancer

Abstract: Disulfidptosis is a newly-identified non-programmed cell death mode with tight associations with glucose metabolism. Elevated glycolysis is an important metabolic feature of tumor cells, which fulfills the energy requirement for their rapid growth and progression. Our present study determined to develop a disulfidptosis and glycolysis related gene (DGRG) risk score signature to predict the prognosis and ICI therapeutic responsiveness for CRC patients. First, the gene expression and clinical profiles for CRC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It revealed that the inhibition of glycolysis promotes cuproptosis, highlighting its potential as a promising therapeutic strategy for the treatment of colorectal cancer [13]. Research findings have indicated that the products generated through glycolysis have the capacity to modulate the activity of disulfidptosis and cuproptosis pathways, ultimately influencing the fate of tumour cells [14, 15]. Given the intricate correlation between programmed cell death (disulfidptosis and cuproptosis) and glucose metabolism, we decided to explore the potential interaction between disulfidptosis‐ and cuproptosis‐related lncRNAs in the pathogenesis of COAD.…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that the inhibition of glycolysis promotes cuproptosis, highlighting its potential as a promising therapeutic strategy for the treatment of colorectal cancer [13]. Research findings have indicated that the products generated through glycolysis have the capacity to modulate the activity of disulfidptosis and cuproptosis pathways, ultimately influencing the fate of tumour cells [14, 15]. Given the intricate correlation between programmed cell death (disulfidptosis and cuproptosis) and glucose metabolism, we decided to explore the potential interaction between disulfidptosis‐ and cuproptosis‐related lncRNAs in the pathogenesis of COAD.…”
Section: Introductionmentioning
confidence: 99%
“…This process can reduce the toxicity of cystine and provide raw materials for the synthesis of glutathione. However, when glucose is deficient, NADPH depletion leads to abnormal accumulation of cystine and other disulfides in cells highly expressing SLC7A11 and triggers disulfidptosis ( 17 ). As a species of high-metabolism and high-energy-consumption cell, tumor cells with high SLC7A11 expression exhibit a stronger disulfidptosis response when glucose is depleted ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Given the strong relationship between the two pathways and their ability to combat cancer, they have been identified as valuable indicators for predicting colorectal cancer prognosis and immunotherapy response. 13 Their ability and mechanism in BC, however, are unknown.…”
mentioning
confidence: 99%